Pengaruh Pemberian ASI Eksklusif terhadap Amenorrhea Laktasi di Indonesia: Influence of Exclusive breastfeeding behaviour with Lactation Amenorrhe in Indonesia - Mona Safitri Fatiah; Yane Tambing; Robani Catursaptani (Jurnal Bidan Cerdas, 2022)
Introduction: The long return of menstruation in postpartum mothers is strongly influenced by the exclusive breastfeeding behavior. In Indonesia is still relatively low compared to other countries, where the median return of menstruation in postpartum mothers in Indonesia is 2 months. The purpose of this study was to look at the influence of exclusive breastfeeding on lactation amenorrhea. Methode: This research is a quantitative research with cross sectional research design with research samples are women who have married aged 15-49 years, amounting to 10,143 people. This study uses SDKI data in 2017 with survival analysis. The results of this study do show the influence of exclusive breastfeeding on lactation amenorrhea after being controlled by confoding variables in the form of education, age, parity, residence and the use of birth control (p value 0,048 with an HR value of 2,32 (95% CI=1,98 – 2,49).  The recommendation of this study is the need to increase KIA method related to the intensity and frequency of breastfeeding from mother to baby.